Local Sustained Chemotherapy of Pancreatic Cancer Using Endoscopic Ultrasound-Guided Injection of Biodegradable Thermo-Sensitive Hydrogel - Yang D; Ning J; Liao X; Jiang H; Qin S (International Journal of Nanomedicine, 2023)
Dan Yang, Jing Ning, Xiaomin Liao, Haixing Jiang, Shanyu Qin Department of Gastroenterology, the First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of ChinaCorrespondence: Shanyu Qin, Department of Gastroenterology, the First Affiliated Hospital of Guangxi Medical University, No. 6. Shuangyong Road, Nanning, Guangxi, 53000, People’s Republic of China, Tel +86 139 7711 0511, Email qinshanyu@gxmu.edu.cnPurpose: Endoscopic ultrasound-guided fine-needle injection (EUS-FNI) offers a promising minimally invasive approach for locally targeted management of advanced pancreatic cancer. However, the efficacy is limited due to the rapid plasma clearance of chemotherapeutic agents. Injectable hydrogels can form drug release depots, which provide a feasible solution for optimizing targeted chemotherapy through EUS-FNI.Methods: A drug delivery system was developed, consisting of gemcitabine (GEM) and thermo-sensitive hydrogel (PLGA-PEG-PLGA, PPP). The injectability, gel formation ability, biocompatibility and sustained drug delivery properties of PPP hydrogel were verified in vitro and in vivo. The effects of GEM/PPP hydrogel on cell proliferation, invasion, metastasis, and apoptosis were explored through co-culturing with PANC-1 cells. The therapeutic effects of GEM/PPP hydrogel on xenograft mice were compared with those of GEM, ethanol and polidocanol using the precisely targeted EUS-FNI technology. Tumor sections were examined by H&E, Ki-67, and TUNEL staining.Results: GEM/PPP hydrogel exhibited excellent injectability, biocompatibility, and the capability of sustained drug delivery for up to 7 days by forming a gel triggered by body temperature. It demonstrated the best therapeutic effects, significantly reducing proliferation, invasion and migration of PANC-1 cells while promoting apoptosis. After precise injection using EUS-FNI technology, GEM/PPP hydrogel resulted in a reduction of tumor weight by up to 75.96% and extending the survival period by 14.4 days with negligible adverse effects. Pathological examination revealed no systemic toxicity and significant apoptosis and minimal proliferation as well.Conclusion: The combination of GEM/PPP hydrogel and EUS-FNI technology provides an optimal approach of precise chemotherapy for pancreatic cancer, builds a bridge for clinical translation of basic research, and brings great hope for innovation of minimally invasive treatment modalities. The first-hand EUS image data obtained in this study also serves as a crucial reference for future clinical trials.Keywords: drug delivery systems, thermo-sensitive hydrogel, endoscopic ultrasound-guided fine needle injection, pancreatic cancer, translational medical research